BANANA BOOM ICE-BREAKING IN EFL CLASSROOM: STUDENTS’ EXPERIENCES - Wahyuni, Atika; Hz, Benni Ichsanda Rahman (University of Kuningan, 2024)
Banana Boom Ice-breaking is one of the most popular activities in the classroom. This study aims to investigate the impact of Banana boom ice-breaking activities on students' enthusiasm for learning and their English skills. This research uses qualitative case study research to know what students felt after doing Banana Boom Ice-breaking. The participants in this study were Junior High School students in Medan, the totalling 28 students in class IX. The data were analysed in two ways: in quantitative methods using content analysis and in qualitative methods using qualitative interpretation based on interviews with participants. The questionnaire consisted of 15 questions that were filled in by 28 students 9th class. The results show that more than half of the students who filled out the questionnaire experienced changes after doing ice breaking. Moreover, in terms of assignments, Banana Boom Ice-breaking can improve students' English skills, which can be seen from the results of this study. It is suggested that educators consider integrating Banana Boom Ice-breaking and similar engaging activities into their teaching practices to enhance students' enthusiasm for learning and foster improvements in their English language skills.